Eksplorisasi Peningkatan Literasi Baca Tulis dan Pemahaman Fiqih Melalui Penggunaan Buku ABACAGA Cepat - Sholihah, Faridatus; Sidiq, Muhammad Abdul Halim; Muttaqin, Ahmad Ihwanul; Ulumudin, Ihya’ (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to explore the improvement of reading–writing literacy skills and understanding of fiqh through the use of the ABACAGA Fast Book as an innovative learning medium for Indonesian immigrant children in Malaysia. This research employed a qualitative approach with a case study method, conducted over one month at PKBM PNF KBRI Malaysia. The findings revealed that the use of the ABACAGA Fast Book significantly improved the children’s ability to read, write, and understand basic Indonesian vocabulary. Children who initially struggled to recognize letters began reading simple words and sentences after four weeks of intensive mentoring. Moreover, the integration of basic fiqh materials such as the procedures of wudu, shalat, and daily manners enhanced the students’ religious understanding and practice. The ABACAGA Fast Book proved to be an effective learning tool for promoting literacy in a joyful, contextual, and spiritually meaningful way among Indonesian immigrant children, especially in non-formal education settings abroad.